Hetrombopag treatment for immune thrombocytopenia in pregnancy refractory to corticosteroids and intravenous immunoglobulin: a case report - Pang, Luyi; Yu, Feng; Yang, Xiaoyang (Frontiers in Medicine, 2025)
Pregnancy can lead to the recurrence or exacerbation of immune thrombocytopenia (ITP). Currently, first-line treatments of low-dose corticosteroids or intravenous immunoglobulin are considered safe and effective for both pregnant women and fetuses. However, there is no well-established treatment option for patients who are refractory to these medications. Herein, we report a case of a 31-year-old pregnant woman with recurrent and refractory ITP who was safely and effectively treated with hetrombopag, with no influence on the infant's platelet count. This case explores a new treatment option for the management of recurrent and refractory ITP in pregnancy.